Self-assembled π-conjugated organic nanoplates: from hexagonal to triangular motifs. Issue 50 (9th May 2016) - Martínez-Tong, Daniel E.; Gbabode, Gabin; Ruzié, Christian; Chattopadhyay, Basab; Schweicher, Guillaume; Kennedy, Alan R.; Geerts, Yves H.; Sferrazza, Michele
Abstract : The formation of triangular nanoplates of an organic semiconducting compound is discussed by considering enhanced solvent/molecule interactions. Abstract : Organic semiconducting materials in confined geometries present interesting properties connected to change or the coexistence of molecular organizations, depending on their characteristic scales. In this work the preparation and structural characterization of self-assembled π-conjugated organic nanoplates of 2, 7-diperfluorohexyl-[1]benzothieno[3, 2, b ]benzothiophene are studied. These nanostructures were prepared by spin coating, implementing a fast precipitation method. We observed an evolution of the nanostructures from hexagonal towards triangular nanoplates, possibly driven by enhanced solvent/molecule interactions, and accompanied by the formation of a new polymorph.